(untitled) (New York, 1998)
This handbook discusses morphology, anatomy, toxonomy,and cultivars...details soil and climatic requirements, propagation, cultural practices, harvesting, and pest and disease control...explains postharvest handling...describes the chemical constituents of each vegetable...
Kỹ thuật chế biến rau quả
Keywords: Truck farming,Vegetables